Художній тип селянина в оповіданні Грицька Григоренка «Переселенці (3 дому і додому)» - Грабенко, Т. (Літературознавчі обрії. Праці молодих учених, 2010)
The author analyses similar types of peasants in the short story by Grytsko Grygorenko «Settlers (From home to home)» and researches the main reasons of migration in XIX–XX centuries. In this case it is very important to accentuate the special character’s behavior due to difficult living conditions.